Reinforced concrete design to Eurocode 2 - Mosley, W. H. (William Henry) (Palgrave Macmillan, 2007)
Provides an introduction to the principles and methods used in the design of reinforced and prestressed concrete structures. This book contains examples to illustrate the various aspects of design involved. It is useful students and practitioners and offers a guide to the basic theory and to design procedures.